An integrated framework of joint venture success. (2016) - Dubey, Rita
It has been widely accepted that majority of joint ventures (JVs) fail to perform as per expectations. While existing research has looked at factors that influence the success and failure of alliances, such research has been largely scattered, focusing either on a particular set of factors or on a particular stage of alliance life cycle. This paper develops a comprehensive framework of firm-level and alliance-level factors across the formation, initialisation and management stages of a JV that influence its success. The findings are based on primary interviews conducted with the top management executives including CEOs of three JVs of a leading player in the Indian retail sector.